Development of National Unity and Political Bodies in Youth Organizations. Study of Christian Student Organizations, Merauke Branch - Grensita Lewakabessy; Vinsenco R. Serano (PAPSEL Research and Consulting, 2024)
The aim of this research is to provide information and find solutions to the problems faced in developing youth organizations. There are factors discussed in detail in this work, apart from solving problems and developing solutions for good change for Karang Taruna and Kesbangpol so that better communication can be built. It is hoped that this work can become a reference for youth organizations registered with Kesbangpol in the future. This research is qualitative research and uses the informant method (interviews). The research results show that there is still a lack of coordination between Kesbangpol and Karang Taruna in Merauke Regency, so that there is still a large discontinuity between the two components that must be connected.